USE OF MOBILE PHONES AS RESEARCH INSTRUMENT FOR DATA COLLECTION - Pakhare, A P; Bali, S; Kalra, G (Indian Journal of Community Health, 2013)
Data collection is a crucial step in any research design or program. In order to be analysed, this collected data needs to be entered into aspreadsheet or statistical software. Transcribing paper based data is time consuming and often associated with errors. Such errors may be due toan inability to read the data-collector’s handwriting,human mistakes during data entry etc. A system wherein data automatically gets transcribed and uploaded in a database during data collection would be of immense use in this situation. A possible solution for this is mobile phone based data collection, a type of electronic data capture method wherein the processes of data collection and data entry are merged1. Initially electronic data collection was done by hand-helddevices such as Personal Digital Assistants (PDAs). However with the entry of the newer and more sophisticated smartphones in the market,there is a growing possibility of extendingthe success achieved on PDAs to a phone-based platform2. Withthe advent of newer technology software solutions this process can even be done on a standard entry level mobile phone. This paper discusses the use and advantages of using mobile phones for data collection and also provides information about resources for mobile based data collection.